Associations between physical activity, positive affect, and self-regulation during preschoolers' everyday lives - Ludwig, Katja; Rauch, Wolfgang (Mental health and physical activity, 2018)
Objective - Previous research on the beneficial effects of physical activity mostly focused on adult samples, although daily physical activity engagement is crucial for children's healthy development. The current study examines associations between preschool-aged children's physical activity, positive affect, and self-regulation during their everyday lives. Both direct and indirect associations between physical activity, positive affect, and self-regulation were investigated. - Methods - For seven consecutive days, 98 children aged four to six years wore a tri-axial accelerometer (ActiGraph wGT3X-BT) to assess their moderate-to-vigorous physical activity (MVPA). During this week, parents rated their children's daily positive affect and self-regulation every evening either by an online questionnaire or via a phone interview. - Results - A multilevel structural equation model revealed direct positive associations between daily MVPA and positive affect (within-person level) and between positive affect and self-regulation (within- and between-person levels). There were no direct positive associations between MVPA and self-regulation (within- and between-person level); at the within-person level, a small, unexpected negative association between MVPA and emotional self-regulation was found. MVPA and self-regulation were indirectly related through positive affect on a daily basis. - Conclusions - Engaging in more MVPA than usual on a given day was positively associated with preschoolers' daily positive affect, which was associated with higher daily self-regulation levels. Whereas physical activity seems to have short-term associations on a daily basis, positive affect seems to facilitate children's self-regulation skills both intra- and inter-individually.
Gesehen am 18.07.2019